Systemic Design and Evaluation of Ticagrelor-Loaded Nanostructured Lipid Carriers for Enhancing Bioavailability and Antiplatelet Activity - Son, Gi-Ho (Pharmaceutics, 2019)
Ticagrelor (TGL), a P2Y(12) receptor antagonist, is classified as biopharmaceutics classification system (BCS) class IV drug due to its poor solubility and permeability, resulting in low oral bioavailability. Nanostructured lipid carriers (NLC) are an efficient delivery system for the improvement of bioavailability of BCS class IV drugs. Hence, we prepared TGL-loaded NLC (TGL-NLC) to enhance the oral bioavailability and antiplatelet activity of TGL with a systemic design approach. The optimized TGL-NLC with Box–Behnken design showed a small particle size of 87.6 nm and high encapsulation efficiency of 92.1%. Scanning electron microscope (SEM), differential scanning calorimetry (DSC), and powder X-ray diffraction (PXRD) were performed to investigate the characteristics of TGL-NLC. Furthermore, TGL-NLC exhibited biocompatible cytotoxicity against Caco-2 cells. Cellular uptake of TGL-NLC was 1.56-fold higher than that of raw TGL on Caco-2 cells. In pharmacokinetic study, the oral bioavailability of TGL-NLC was 254.99% higher than that of raw TGL. In addition, pharmacodynamic study demonstrated that the antiplatelet activity of TGL-NLC was superior to that of raw TGL, based on enhanced bioavailability of TGL-NLC. These results suggest that TGL-NLC can be applied for efficient oral absorption and antiplatelet activity of TGL.